Analisis Pendapatan Asli Daerah (PAD) sebagai Upaya Pelaksanaan Otonomi Daerah di Kabupaten Toraja Utara Periode 2016-2020 - Ardiansyah Ali; Nursyam AR (Faculty of Economics and Business, Universitas Mahasaraswati Denpasar, 2023)
The existence of a policy to manage government independently in the form of regional autonomy makes every decision more strategic in increasing local revenue sources to the maximum. The purpose of this study was to analyze the regional own-source revenue (PAD) of North Toraja Regency in 2016-2020. Quantitative descriptive method is used to describe the contribution ratio and growth ratio in local own revenue (PAD). The results of this study indicate that the contribution of local taxes to local own-source revenue (PAD) is in the sufficient category, while for contributions in the very poor category obtained from the results of the management of separated assets. For the growth ratio, the results fluctuated greatly from 2016-2019, but a drastic decline occurred in 2020, this was due to the covid-19 pandemic that hit North Toraja Regency.